What do we know about the future of measuring food systems? - Fanzo, Jessica; Carducci, Bianca; Puma, Michael (International Food Policy Research Institute, 2025)
Many food systems-related databases, tools, and dashboards are available, but to ensure these tools are helpful for decision-makers, they must be harmonized and their sophistication increased to capture trade-offs and synergies.